Characterisation of the genetic relationship between the domains of sleep and circadian‐related behaviours with substance use phenotypes. (29th May 2022) - Hatoum, Alexander S.; Winiger, Evan A.; Morrison, Claire L.; Johnson, Emma C.; Agrawal, Arpana
Abstract: Sleep problems and substance use frequently co‐occur. While substance use can result in specific sleep deficits, genetic pleiotropy could explain part of the relationship between sleep and substance use and use disorders. Here we use the largest publicly available genome‐wide summary statistics of substance use behaviours ( N = 79, 729–632, 802) and sleep/activity phenotypes to date ( N = 85, 502–449, 734) to (1) assess the genetic overlap between substance use behaviours and both sleep and circadian‐related activity measures, (2) estimate clusters from genetic correlations and (3) test processes of causality versus genetic pleiotropy. We found 31 genetic correlations between substance use and sleep/activity after Bonferroni correction. These patterns of overlap were represented by two genetic clusters: (1) tobacco use severity (age of first regular tobacco use and smoking cessation) and sleep health (sleep duration, sleep efficiency and chronotype) and (2) substance consumption/problematic use (drinks per day and cigarettes per day, cannabis use disorder, opioid use disorder and problematic alcohol use) and sleep problems (insomnia, self‐reported short sleep duration, increased number of sleep episodes, increased sleep duration variability and diurnal inactivity) and measures of circadian‐related activity (L5, M10 and sleep midpoint). Latent causal variable analyses determined that horizontal pleiotropy (rather than genetic causality) underlies a majority of the associations between substance use and sleep/circadian related measures, except one plausible genetically causal relationship for opioid use disorder on self‐reported long sleep duration. Results show that shared genetics are likely a mechanism that is at least partly responsible for the overlap between sleep and substance use traits. Abstract : We explored the genetic correlation and plausible correlation between several sleep and substance use phenotypes using genome‐wide association data and techniques. Sleep and substance use behaviors overlap due to genetic pleiotropy. There are two dimensions of sleep and substance use overlap: a sleep health and tobacco cluster (smoking cessation and initiation with sleep efficiency measures) and a sleep problem and heavy substance use cluster (insomnia, self‐reported sleep duration measures, and drinks per week).